Resonant scattering measurement for 11C using thick target in inverse kinematics. Issue 1 (1st September 2022) - Kaur, Gurpreet; Guimarães, V.; Zamora, J.C.; Assunção, M.; Alcantara-Nunez, J.; de Lara, A.L.; Zevallos, E.O.N.; Ribeiro, J.B.; Lichtenthäler, R.; Pires, K.C.C.; Santos, O.C.B.; Morcelle, V.; et al.
Abstract: The resonant scattering of 10 B+ p reaction was measured at θ c.m. = 180°, 170°, 160°, 150° and 140° using a 35.93 MeV 10 B beam to investigate the spectroscopy of 11 C with the thick target inverse kinematic method at RIBRAS facility, IFUSP, São Paulo. Influence of the stopping power uncertainty on the resonant scattering cross section values for 11 C in the 10 B( p, p ) 10 B reaction is shown. The data measured for the reaction channels p ( 10 B, α ) and p ( 10 B, 3 He) is also presented. Interestingly, the cross sections for the 3 He channel are observed upto 2 MeV below the lowest energy measurement available in literature.